-9-6k+9-(2k)=

Simple and best practice solution for -9-6k+9-(2k)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9-6k+9-(2k)= equation:


Simplifying
-9 + -6k + 9 + -1(2k) = 0

Remove parenthesis around (2k)
-9 + -6k + 9 + -1 * 2k = 0

Multiply -1 * 2
-9 + -6k + 9 + -2k = 0

Reorder the terms:
-9 + 9 + -6k + -2k = 0

Combine like terms: -9 + 9 = 0
0 + -6k + -2k = 0
-6k + -2k = 0

Combine like terms: -6k + -2k = -8k
-8k = 0

Solving
-8k = 0

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Divide each side by '-8'.
k = 0

Simplifying
k = 0

See similar equations:

| .2m=22 | | -8h+3(1-5)=3b+37 | | 6(7y-5)=12y | | -(5a-4)+4a=5 | | 2c(9-5c)+6(c^2-c)=0 | | 3xy+x=8 | | 18x-2y+3-3x-3y= | | 4x+6+3=7 | | -(1+7x)+-6(-7+-x)=36 | | 9x^2-12y=15 | | 8h+3(1-5)=3b+37 | | 2x+5=7-4x | | 128v^2+448v+392=0 | | -10y+18=-3(5y-70)+5 | | 6x-3=27x-11 | | 2x+7x+10=x | | x^2+20x+12000=0 | | 12(x-2)=2(6x-3)-18 | | 10+h=54 | | -(3-2N)+7N=(N+3)3 | | -6(x-12)+2(x+2)=x-9 | | -6(6y+2)-(-5y-8)=2 | | 1.96=r^2+2r+1 | | -4+2n+16=n+7 | | 1x-2(x+10)=12 | | 7x-9=-4x+90 | | 3(x+5)=3x | | 12*n=12*6 | | -(3-2N)+7N=(N+3) | | 18a-22=-4(1-6a) | | N*1=2 | | 50-6x=-46 |

Equations solver categories